Os desafios da educação na perspectiva inclusiva: o que pensam os professores? - Monteiro, Jória Pereira (Universidade do Estado do Amazonas, 2019)
Inclusive educational practice still seems to be a great challenge for teachers, a perception constructed from observations made in the internship contexts and also in the place where we act as a teacher. Thus the research is born having as questions if all teachers had difficulty in performing inclusive education in the classroom? If you have difficulties and challenges, what are they? To know these perceptions we propose to develop this study, with a qualitative approach, the bibliographic and field types, having as data collection instruments the questionnaire, applied to both public and private school teachers, in order to know different perceptions of the phenomenon. of inclusive education. Thus, the research did not have a single school as a locus, including 06 teachers who work in schools in the south, east, west, north and rural areas of Manaus. As a research method, the studies were based on the socio-historical perspective. We consider this work relevant because we need to know the teachers' perception to reflect on the pedagogical practice in an educational model that gives opportunity to human development through education in an inclusive perspective. Thus, the study allowed us to know the history of Special Education in Brazil, the perceptions that teachers have about the challenges and possibilities of education from an inclusive perspective, as well as the implementation of methodological strategies that contribute to the integral development of the subjects. Similarly, the study raised an analysis of the post and cons of this inclusive education, from the perspective of teachers.